Improving zakat management with QRIS: A system thinking approach to boost financial literacy and inclusion - Sarasi, Vita; Nugraha, Denny Sidharta; Fadillah, Afrizal; Aulia, Sulthonul; Farras, Joval Ifghaniyafi; Fahri Setiono, Muhammad (Journal of Islamic Economics Lariba, 2025)
IntroductionZakat management in Indonesia faces operational inefficiencies, low digital adoption, and limited financial inclusion, especially in underserved areas. The introduction of QRIS (Quick Response Code Indonesian Standard) as a digital payment system presents an opportunity to improve zakat collection, transparency, and accessibility. However, systemic barriers such as low zakat literacy, limited trust, infrastructure gaps, and regulatory challenges hinder optimal adoption. ObjectivesThis study aims to analyze the systemic factors influencing QRIS adoption in zakat management. It investigates how variables such as zakat literacy, digital literacy, user trust, infrastructure, and policies interact to affect digital zakat ecosystems in Indonesia.MethodThe research employs a System Thinking approach, utilizing qualitative methods including expert interviews, document analysis, and literature triangulation. A Causal Loop Diagram (CLD) is developed to map feedback loops among macro, micro, interface, and policy-level factors, enabling identification of leverage points for strategic interventions.ResultsFindings reveal that increasing zakat and digital literacy significantly enhances user trust and QRIS adoption, forming a reinforcing feedback loop. However, high transaction costs and inadequate infrastructure create balancing loops that impede adoption. Comparative insights from Malaysia, Pakistan, and Gulf countries support the importance of Shariah compliance and regulatory clarity in building trust.ImplicationsThis study highlights the need for integrated strategies combining financial and digital literacy programs, regulatory reforms, and infrastructure investments to promote equitable and sustainable digital zakat systems in Indonesia. It offers actionable insights for policymakers, Islamic financial institutions, and zakat organizations. Originality/NoveltyThis study contributes to the limited literature on digital zakat management by applying a System Thinking approach—an analytical method rarely used in Islamic finance. Using a Causal Loop Diagram (CLD), it visualizes dynamic interconnections and feedback loops between trust, cost, infrastructure, and Shariah legitimacy. This feedback-based framework offers a more holistic view than conventional linear models such as TAM or UTAUT, providing practical insights for improving Sharia-compliant financial inclusion.